Bayesian probability theory : applications in the Physical Sciences - Linden, Wolfgang von der; Dose, Volker; Toussaint, Udo von (Cambridge : Cambridge University Press, 2014)
From the basics to the forefront of modern research, this book presents all aspects of probability theory, statistics and data analysis from a Bayesian perspective for physicists and engineers. The book presents the roots, applications and numerical implementation of probability theory, and covers advanced topics such as maximum entropy distributions, stochastic processes, parameter estimation, model selection, hypothesis testing and experimental design. In addition, it explores state-of-the art numerical techniques required to solve demanding real-world problems. The book is ideal for students and researchers in physical sciences and engineering.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Probabilities; Bayesian statistical decision theory